Long-term surgical outcomes of levator resection in patients with Marcus-Gunn jaw-winking ptosis. (4th March 2022) - Al-Essa, Rakan S.; Althaqib, Rawan N.; Kikkawa, Don O.; Alsuhaibani, Adel H.
ABSTRACT: Purpose: To report long-term surgical outcomes of a series of MGJWS patients with moderate ptosis who underwent levator resection. Materials and Methods: A retrospective review of medical records of 10 MGJWS patients with moderate ptosis who underwent levator resection was performed in two major eye centers in Riyadh, Saudi Arabia from January 1987 to December 2019. Clinical features, pre-operative and post-operative data of the 10 patients were recorded. Outcome Measures: Long-term upper eyelid position. Results: The mean patient age at presentation was 5.4 years. Seven patients were female and three were male. All patients had moderate ptosis with marginal reflex distance ranged from 1 to 2 mm. The mean age at surgery was 9.5 years. After initial good ptosis correction for all patients, seven of them had a recurrence of ptosis several months after levator resection. Conclusions: Levator resection in MGJWS patients with moderate ptosis and good levator function is associated with a high rate of ptosis recurrence and less predictable surgical results.